Physical inactivity, gender and culture in Arab countries: a systematic assessment of the literature - Eman Sharara; Chaza Akik; Hala Ghattas; Carla Makhlouf Obermeyer (BMC, 2018)
Abstract Background Physical inactivity is associated with excess weight and adverse health outcomes. We synthesize the evidence on physical inactivity and its social determinants in Arab countries, with special attention to gender and cultural context. Methods We searched MEDLINE, Popline, and SSCI for articles published between 2000 and 2016, assessing the prevalence of physical inactivity and its social determinants. We also included national survey reports on physical activity, and searched for analyses of the social context of physical activity. Results We found 172 articles meeting inclusion criteria. Standardized data are available from surveys by the World Health Organization for almost all countries, but journal articles show great variability in definitions, measurements and methodology. Prevalence of inactivity among adults and children/adolescents is high across countries, and is higher among women. Some determinants of physical inactivity in the region (age, gender, low education) are shared with other regions, but specific aspects of the cultural context of the region seem particularly discouraging of physical activity. We draw on social science studies to gain insights into why this is so. Conclusions Physical inactivity among Arab adults and children/adolescents is high. Studies using harmonized approaches, rigorous analytic techniques and a deeper examination of context are needed to design appropriate interventions.